2015
DOI: 10.1039/c4bm00462k
|View full text |Cite
|
Sign up to set email alerts
|

Folate-containing reduction-sensitive lipid–polymer hybrid nanoparticles for targeted delivery of doxorubicin

Abstract: The development and evaluation of folate-targeted and reduction-triggered biodegradable nanoparticles are introduced to the research on targeted delivery of doxorubicin (DOX). This type of folate-targeted lipid-polymer hybrid nanoparticles (FLPNPs) is comprised of a poly(D,L-lactide-co-glycolide) (PLGA) core, a soybean lecithin monolayer, a monomethoxy-poly(ethylene glycol)-S-S-hexadecyl (mPEG-S-S-C16) reduction-sensitive shell, and a folic acid-targeted ligand. FLPNPs exhibited high size stability but fast di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 36 publications
0
32
1
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18] We previously reported the preparation of a new type of hybrid nanoparticle LPNPs using an amphiphilic reduction-sensitive polymer of monomethoxy-poly(ethylene glycol)-S-S-hexadecyl (mPEG-S-S-C 16 ) to achieve intracellular release and then improve the therapeutic effect. [19][20][21] The amphiphilic polymer mPEG-S-S-C 16 containing a disulfide bond could maintain the stability of this formulation and serve as a switch to trigger drug release. The system of LPNPs was evaluated in vitro and in vivo and was proven as a potential drug carrier.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] We previously reported the preparation of a new type of hybrid nanoparticle LPNPs using an amphiphilic reduction-sensitive polymer of monomethoxy-poly(ethylene glycol)-S-S-hexadecyl (mPEG-S-S-C 16 ) to achieve intracellular release and then improve the therapeutic effect. [19][20][21] The amphiphilic polymer mPEG-S-S-C 16 containing a disulfide bond could maintain the stability of this formulation and serve as a switch to trigger drug release. The system of LPNPs was evaluated in vitro and in vivo and was proven as a potential drug carrier.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Disulfide bond is stable under normal physiological conditions yet responsive to the reductive environment (eg, GSH) of intracellular fluids in cancer cells, indicating that disulfide bonds can be used as the linker of hydrophilic and hydrophobic portions in the redox-sensitive polymeric micelles for controlling the delivery of intracellular drug. 22 Here, we synthesized a redox-sensitive F127-SS-TOC polymer using a disulfide bond to link F127 and TOC, which formed nanomicellar structures in aqueous solution and ruptured in the presence of glutathione (GSH, 2-10 mM) ( Figure 1) owing to a redox reaction. F127-SS-TOC polymer was synthesized and confirmed with 1 H nuclear magnetic resonance spectra ( 1 H NMR) and Fourier transform infrared spectra (FTIR).…”
Section: Introductionmentioning
confidence: 99%
“…The lipid-polymer hybrid nanoparticles, which have various advantages of polymeric nanoparticles and liposomes, have become a robust delivery platform with properties such as excellent stability, tunability, high drug encapsulation, and sustained drug release. 28 Liposome was an ideal CAs carrier to clearly display the extent of cancer and monitors the treatment effect in real time. 29,30 In addition, previous research has suggested that CAs have better MRI contrast effect or stronger fluorescence intensity when the CAs were released from the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%